ANAPHYLACTIC SHOCK DUE TO PROPHYLACTIC ANTIBIOTICS IN PLANNED SECTIO CESAREAN : A CASE REPORT - Porman Surtana Siahaan, Hatsari Marintan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Anaphylactic reactions during pregnancy are complex to diagnose and manage, potentially ranging from mild symptoms to life-threatening situations for both the mother and fetus. With an incidence varying from 1.44 to 2.7 cases per 100,000 births and subtle, overlapping symptoms with other obstetric emergencies, accurate identification remains a challenge. Despite being underdiagnosed, severe anaphylactic events during pregnancy share symptoms with other critical conditions, making differentiation intricate. Prior reviews and recent data underscore the necessity for guidelines and public health actions, emphasizing the importance of vigilance and specific management strategies in obstetrics. Case report: This case involves Ny. S, a 33-year-old pregnant woman undergoing an elective C-section, who developed an allergic reaction to Cefazolin, necessitating an emergency procedure and subsequent ICU admission due to anaphylactic complications. Patient at 38 weeks pregnant, encountered an unexpected allergic reaction during a planned C-section, necessitating an emergency procedure. Post-surgery, she experienced severe complications, including pulmonary and laryngeal edema, requiring intensive care. With prompt medical attention and a comprehensive treatment plan, including medications and careful monitoring, her condition stabilized over several days. By October 21, 2023, she showed significant improvement, allowing her discharge with scheduled follow-up care. Discussion: The discussion encompasses the complexity of diagnosing anaphylaxis during pregnancy, highlighting challenges in laboratory confirmation, management protocols mirroring non-pregnant guidelines, and the importance of coordinated medical care to avert adverse maternal and fetal outcomes. It emphasizes the need for standardized protocols and consensus among healthcare providers to effectively manage maternal anaphylaxis, reflecting on the rarity of this condition and the potential risks it poses to both the mother and fetus.     Conclusion:  Anaphylactic reaction during an elective C-section, prompting urgent medical intervention involving mechanical ventilator support and meticulous care. Patient’s subsequent recovery and discharge, along with fluctuating lab results indicating an acute immune response, underscore the complexity of diagnosing and managing maternal anaphylaxis, emphasizing the need for standardized protocols and coordinated healthcare approaches.